Konservasi Blue Economy untuk Meningkatkan Kesejahteraan Masyarakat Daerah Istimewa Yogyakarta - Maria Griselda Delwela Papur; Gabriella Angela Sitorus; Ester Amelia Tambun Saribu; Josephine Wuri (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2024)
The blue economy is a development concept that focuses on the sustainable use of marine resources. This concept has great potential to improve the welfare of people in the Special Region of Yogyakarta (DIY). This study aims to examine the conservation of the blue economy as a means of enhancing the well-being of the DIY community. This study used a quantitative approach with multiple linear regression analysis methods. Data was obtained from the Ministry of Fisheries and Marine Affairs and the Central Bureau of Provincial Statistics DIY for the period 2020–2023. The results of the analysis show that the variables of conservation, fish farming, and land area have a positive and significant influence on community welfare. By optimizing marine economic sectors such as fisheries, marine resource conservation, and fish farming land area, the implementation of the blue economy can increase people's income and standard of living. However, the successful implementation of the blue economy also depends on collaboration between the government, the private sector, and the community.